Characterization of tellurium dioxide thin films obtained through the Pechini method - Bataliotti, Murilo Dobri [UNESP]; Costa, Francine Bettio [UNESP]; Minussi, Fernando Brondani [UNESP]; Araújo, Eudes Borges [UNESP]; de Lima, Nelson Batista; Moraes, João Carlos Silos [UNESP] (Springer Nature, 2022)
Tellurium dioxide (TeO2) thin films were deposited on silicon substrates through the Pechini method, after which they were heat treated at different temperatures. The heat treatment temperatures were defined from the thermogravimetry-differential scanning calorimetry (TG-DSC) data of the precursor gel. The effects of the heat treatment on the structural properties were investigated through X-ray diffraction (XRD), atomic force microscopy, and Raman spectroscopy. The TG-DSC data showed four different weight loss steps due to the reduction of telluric acid to tellurium, the removal of the excess ethylene glycol, the decomposition of citric acid, and the degradation of polyester. The XRD and Raman data showed the presence of the γ- and α-TeO2 phases in the films treated at 400–500 °C. Lattice parameters of the observed crystalline phases were determined by Rietveld refinement, with which it was possible to evaluate the crystallite size and microstrain using the Williamson-Hall method. The heat treatment temperature directly influenced the crystallite size and the surface roughness of the films, which showed similar behaviors with the temperature. [Figure not available: see fulltext.].
Keywords: Atomic force microscopy; Rietveld refinement; Sol-gel; Tellurite dioxide; Thin Films; X-ray diffraction